Forensic psychiatric experts under the legal microscope - Grønnerød, Cato (Legal and criminological psychology, 2016)
Purpose. We examined how 157 legal professionals view the role and performance of forensic psychiatric experts (psychiatrists and psychologists) in court, and what experiences they have with the experts. Methods. The participants filled in an online survey with ratings and open-ended questions. Results. Their experience was fairly limited, but the general impression was one of overall satisfaction with the experts. Experience was not only valued but also clarity in language and presentation were important, together with verifiability and thoroughness. The ability or willingness to express doubt was also emphasized. In addition, a significant proportion felt they had observed differences between psychologists and psychiatrists, and they preferred psychiatrists based on a perception of higher professional skills. Conclusions. Despite media uproars after controversial cases, the Norwegian system of court-appointed experts received a positive review from the legal professionals; they report an overall positive experience with forensic psychiatric experts.